2015
DOI: 10.1063/1.4936667
|View full text |Cite
|
Sign up to set email alerts
|

Al4SiC4 wurtzite crystal: Structural, optoelectronic, elastic, and piezoelectric properties

Abstract: International audienceNew experimental results supported by theoretical analyses are proposed for aluminum silicon carbide(Al4SiC4). A state of the art implementation of the density functional theory is used to analyze the experimental crystal structure, the Born charges, the elastic properties, and the piezoelectricproperties. The Born charge tensor is correlated to the local bonding environment for each atom. The electronic band structure is computed including self-consistent many-body corrections. Al4SiC4ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 51 publications
(91 reference statements)
6
39
0
Order By: Relevance
“…Liao et al [11] investigated the bonding characteristics, atomic deformation modes and ideal mechanical strengths of Al 4 SiC 4 , it was concluded that the structural failure occurring in tensile deformation simulation is due to the existence of intrinsic brittleness in Al 4 SiC 4 . In a very recent work, Pedesseau and coworkers [12] have addressed the optoelectronic, elastic and piezoelectric properties of Al 4 SiC 4 . Most importantly, the authors employed the self-consistent many-body perturbation method to calculate the band gap of the same phase.…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al [11] investigated the bonding characteristics, atomic deformation modes and ideal mechanical strengths of Al 4 SiC 4 , it was concluded that the structural failure occurring in tensile deformation simulation is due to the existence of intrinsic brittleness in Al 4 SiC 4 . In a very recent work, Pedesseau and coworkers [12] have addressed the optoelectronic, elastic and piezoelectric properties of Al 4 SiC 4 . Most importantly, the authors employed the self-consistent many-body perturbation method to calculate the band gap of the same phase.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of typical mm size Al 4 SiC 4 platelets was investigated by TEM observations and XRD analysis and reported to be hexagonal (Space group P6 3 mc), their c-axis being perpendicular to the crystal surface [6,10] …”
Section: Methodsmentioning
confidence: 99%
“…The local density approximation (LDA) was used for the exchange-correlation functional [23,24]. Atomic valence configurations were similar to the ones used in previous DFT simulations of the ground state [5,6,18]. A plane-wave basis set with an energy cut-off of 950 eV was used to expand the electronic wave-functions.…”
Section: Dft Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…6, Al 4 SiC 4 owns a P6 3 mc space group and a hexagonal crystal structure which can be described as layered structure stacked with the 4H-SiC type units and Al 4 C 3 type units alternative along the c-axis [35,36]. It has been reported that the development of the hexagonal grains depends on the grain growing rate of (0010) and (1 10) planes which is closely related to the surface energy.…”
Section: Grain Growth Mechanismmentioning
confidence: 99%